2012
DOI: 10.1007/s12519-012-0365-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of hypoxemia in Indian children with acute respiratory tract infection presenting to pediatric emergency department

Abstract: Chest wall retraction was found to be the most sensitive indicator, and cyanosis was the most specific indicator for hypoxemia. Of all the clinical signs and symptoms of hypoxemia, none had all the attributes of being a good predictor. A new hypoxemia score has been designed using a combination of clinical signs and symptoms to predict the need for supplemental oxygen therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 11 publications
2
17
1
Order By: Relevance
“…14 The prevalence of hypoxemia documented in various studies with a variation. The present study showed 48%, the prevalence of hypoxemia was more [14][15][16][17] when compared to earlier studies in India. There were 24.4% female and 75.6% male children found without hypoxemia as compared to 37.5% female and 62.5% male children had hypoxemia but the gender differences between groups were statistically insignifi cant which was supported by Motwani et al (2015) 10 observed that the difference between male and females, as regarding to prevalence of hypoxemia was not signifi cant.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…14 The prevalence of hypoxemia documented in various studies with a variation. The present study showed 48%, the prevalence of hypoxemia was more [14][15][16][17] when compared to earlier studies in India. There were 24.4% female and 75.6% male children found without hypoxemia as compared to 37.5% female and 62.5% male children had hypoxemia but the gender differences between groups were statistically insignifi cant which was supported by Motwani et al (2015) 10 observed that the difference between male and females, as regarding to prevalence of hypoxemia was not signifi cant.…”
Section: Discussioncontrasting
confidence: 45%
“…12 Findings of the study revealed that grunting (p=0.009), nasal fl aring (p=0.008), subcostal (p=0.001) and intercostal (p=0.000) retractions were highly but suprasternal retraction was signifi cantly (p=0.024) associated with hypoxemia which is in agreement with various other studies have reported that grunting and nasal fl aring were signifi cantly associated with hypoxemia. 1,18,23 During a study, Rao et al (2012) 16 found that chest wall retraction was found to be the most sensitive indicator, and cyanosis was the most specifi c indicator for hypoxemia. Kuti has also confi rmed the relevance of the study as he recently reported that children that grunt and are centrally cyanosed should preferentially commenced on oxygen therapy even when there is no facility to confi rm hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…inability to feed or drink or cyanosis or respiratory rate >70 breaths/min or severe chest indrawing) are a sensitive combination of clinical signs, although its moderate specificity could be problematic in limited‐resource settings due to the risk of wasting oxygen treating non‐hypoxaemic children . There is no consensus on whether to prioritize sensitivity or specificity of the variables used to build combined models .…”
Section: Introductionmentioning
confidence: 99%
“…2 To date, no consensus has been reached on the importance of specific clinical predictors of hypoxaemia in children with acute respiratory disease, despite the publication of several reports on the subject. [2][3][4][5][6][7] In their systematic review and meta-analysis of the accuracy of symptoms and signs in predicting hypoxaemia in children, Zhang et al found only 11 studies and there was high Heterogeneity in the results across the studies. 8 As the administration of oxygen is of primary importance in these situations, hypoxaemia has to be detected rapidly.…”
Section: Introductionmentioning
confidence: 99%